Impact of typhoons on the ecological environment of the Pearl River Estuary in the summer of 2021—a study of an algal bloom event - Zhang, Xin; Gao, Shan; Ji, Xuanliang; Zhu, Xueming; Zheng, Jingjing; Guo, Shaojing (Frontiers in Marine Science, 2024)
In the summer of 2021, two typhoons, Typhoon Cempaka and Typhoon Lupit, passed through the Pearl River Estuary (PRE), resulting in a noticeable chlorophyll-a (Chla) bloom event on the west side of the PRE. Utilizing a coupled hydrodynamic-ecological model (ROMS-CoSiNE), we investigated the changes in the marine environment during the two-typhoon period and explored the underlying mechanisms involved. Our model effectively reproduces the spatial characteristics of the typhoon-induced algal blooms. The results suggest that the westward invasion of the Pearl River plume has a predominant impact on the alterations in biochemical elements. For further quantitative analyses, we utilized the model to determine the Chla concentration budget in algal bloom region to assess the dominant mechanism, particularly focusing on horizontal advection. Our findings indicated that algal bloom events are mainly attributed to a straightforward physical mechanism, namely, phytoplankton transportation, rather than to nutrient-induced phytoplankton growth. The study also revealed that the different growth processes of the two simulated phytoplankton species did not contribute positively to the increased Chla concentrations. However, further research is needed to investigate the impacts of different phytoplankton functional groups on the marine ecological environment under the influence of typhoons. This study enhances the understanding of the response of ecological environments in coastal areas to typhoons.